Human-centred design of robotic systems and exoskeletons using digital human models within the research project SOPHIA - Susanne Niehaus; Arash Ajoudani; Matteo Bianchi; Guillaume Durandau; Lars Fritzsche; Christian Gaertner; Mohamed Irfan Refai; Massimo Sartori; Huawei Wang; Sascha Wischniewski (Zeitschrift für Arbeitswissenschaft, 2022)
Using a~real workplace as an example, this paper describes how digital human modelling software facilitates planning and simulating work processes. This is closely connected to the ongoing activities and results from the SOPHIA project in which the inferred parameters are used for ergonomic assessments. Moreover, multiple options for digital human modelling, developed in the SOPHIA project, will be presented. In this context, the development process of personalized human models within the project to optimize the worker's ergonomics when performing tasks with a~robotic system or exoskeleton will be described. The paper closes with a~short description of what still needs to be addressed to ensure personalized, reliable and robust digital human modelling for an industrial setting. Practical Relevance: This paper shows the scientific process within the SOPHIA project on the subject of digital human models. This provides an overview of the current state of research, as well as available and innovative approaches for modelling people at the workplace. It is shown to what extent the goal of creating personalized human models to optimize the ergonomics of employees that work with robotic systems or exoskeletons has already been achieved. Therewith, it is displayed which developments can already be used and which components are still missing in order to better simulate and thus enrich the interaction between humans and robots/exoskeletons.
Keywords: 650; Digital Human Modelling; Human-Robot Interaction; Ergonomics; Digitale Menschmodelle; Mensch-Roboter-Interaktion; Ergonomie